Astrology and Matrimony: Social Reinforcement of Religious Beliefs on Marriage Matching in Vietnam - Edoardo Ciscato; Quoc-Anh Do; Kieu-Trang Nguyen (CESifo GmbH, 2024)
This paper demonstrates the prevalence, pervasiveness, persistence, and resilience of a system of non-Big God religious beliefs, in absence of religious organizations and moralizing prescriptions, thanks to a self-fulfilling mechanism based on social insurance. We focus on the Vietnamese's beliefs in marriage fortune predictions by the Taoist astrological system Tử Vi. First, we estimate a structural model of assortative marriage matching and show that such beliefs' importance in marriage formation amounts to 6.5% of that of the entire age and education profile. Second, we estimate the effect of auspiciousness on couples' outcomes while controlling for selection into marriage using the structural model's predictions. Auspicious couples receive 11% more social transfers from their extended family, and up to 28% under hardship, because they are believed to be more harmonious and lucky. They further enjoy more consumption, income, and other welfare measures. We link the system's long-term persistence and resilience to its potential role as a commitment device between families.
Keywords: Z12; J12; D64; G52; O15; D83; D16; 330; non-Big God religion; traditional beliefs; self-fulfilling prophecy; marriage market; social transfers; social insurance; second-order belief; commitment device